Sex specific familial risk in lung cancer through changing histologies in Sweden - Hemminki, Kari; Zitricky, Frantisek; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Akseli (International journal of cancer, 2025)
Familial clustering of lung cancer (LC) is related to shared smoking habits but the contribution of other potential factors such as sex or histology is not well known, and these are the subjects of the present study in Sweden. Family relationships (from Multigeneration register) and diagnosed cancers (from Cancer registry) were obtained from the national registers from 1961 to 2021. The overall familial risk for LC was constant from the 1990s but the male familial risk decreased while the female familial risk doubled at the same time when female incidence doubled. The female familial risk for mother-daughter pairs was higher (SIR = 2.2 [2.0-2.3], N = 716) than for father-son pairs (SIR = 1.6 [1.5-1.8], N = 962). The histology-specific familial risks for adenocarcinoma, squamous cell carcinoma, small cell and large cell carcinoma were highest for concordant histology but also present for discordant histology. The number of family members diagnosed with LC was a strong determinant of familial risk. The novel results showed that familial risk of LC depends on the background incidence of LC and is higher for women compared to men. We demonstrated further an increased familial risk for each of the four histological types of LC which was higher for concordant than discordant histologies but was even detected between discordant histologies suggesting that LC histology is not a genetic trait.
Keywords: dospělí; Carcinoma, Squamous Cell; Švédsko; Female; Adult; ženské pohlaví; nádory plic; Registries; incidence trend; age of onset; lidé; sibling risk; genetická predispozice k nemoci; Genetic Predisposition to Disease; Sex Factors; Incidence; Risk Factors; Adenocarcinoma; Sweden; Male; incidence; Aged; sexuální faktory; spinocelulární karcinom; adenokarcinom; adenocarcinoma; rizikové faktory; Lung Neoplasms; lidé středního věku; registrace; senioři; mužské pohlaví; proband; Middle Aged; Humans